VD_FINDINFO HC / 2011 / 449 vom 27. Juli 2011 - VD Tribunal cantonal (2011)
PRINCIPE DE LA CONFIANCEINTERPRÉTATION DU CONTRAT, PRÊT À USAGE, BAIL À LOYER | 253a al. 1 CO, 269d al. 3 CO, 310 CO, 308 al. 1 let. b CPC (CH), 317 al. 1 CPC (CH)